Students’ Perception On The Use of Songs On Spotify In Learning Figurative Language - Cahyani, Novela; Solusia, Carbiriena (Universitas Negeri Padang, 2025)
Figurative language as an essential component of language that present challenges for students due to its symbolic nature and abstract. In responses, this research explored whether integrating on the use of songs on Spotify, a widely used digital music streaming platform, could enhance students’ understanding and engagement in this area. This study aimed to investigate students’ perception on the use of songs on Spotify in learning figurative language. The researcher employed a descriptive quantitative method using questionnaire as the instrument to gather data in this research, consisting of 35 statements covering the indicators. The instrument had five indicators of figurative language knowledge, strategies, benefits, advantages, and challenges. The sample was selected by using cluster sampling technique. The population of this study which consisted of 23 students of K7 students of the English Department of Universitas Negeri Padang (UNP) academic year 2023. The research findings were the mean score 3.69 that students indicates positive perception. This suggest that on the use of songs on Spotify are perceived as an effective and engaging as learning media in learning figurative language. It can be concluded that the result of this study highlight that students’ perception on the use of songs on Spotify in learning figurative language was positive.